An Application of the Wilkie Model in Analysing Share Price Index in Malaysia - Hafiz, NAM; Ishak, N; Rasedee, AFN (Amer Inst Physics, 2024)
Wilkie investment model is a stochastic investment model that was built by A. D Wilkie in 1984 and was updated in 1995. The model building objective is forecasting. Box-Jenkins method was the basic structure of Wilkie model. It involves various type of forecasting model. Some model handle stationary time series such as autoregressive moving average (ARMA) model while some of them handle non-stationary time series such as autoregressive integrated moving average (ARIMA) model. There are four sub-models in the Wilkie model which is retail price index model, share dividend yield model, share dividend index model and Consols yield model.